LINGUODIDACTIC OPPORTUNITIES FOR FORMING PROFESSIONAL RUSSIAN MEDICAL VOCABULARY FOR MEDICAL STUDENTS (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
This article provides a thorough analysis of the linguodidactic possibilities for developing professional Russian language vocabulary among medical students. The aim of the study is to identify effective ways of mastering professional medical terminology in the process of teaching Russian as a foreign language (RFL/RKI), to improve linguodidactic methods, and to provide practical recommendations. The research conducted a systematic analysis based on the Content and Language Integrated Learning (CLIL) approach, digital technologies (Zoom and Moodle platforms), morphological analysis, interactive exercises, and project-based learning. The results indicate that the use of interactive and integrated methods in forming professional vocabulary can increase students’ communicative competence by 35–45%. The article is of practical importance for higher medical educational institutions in Uzbekistan, particularly Tashkent Medical Academy and other universities with a large number of international students. It proposes adapting linguodidactic opportunities to local conditions. The research findings respond to the demands of digital transformation in modern education and professional training requirements.